ABOUT LAW ENFORCEMENT IN MODERN RUSSIA - A. Kostyukov (Правоприменение)
УДК 340.132The state of law enforcement in modern Russia is analyzed in the article on the basis of judicial statistics. The author gives a critical assessment of the most important decisions of the Constitutional Court of the Russian Federation handed down in 2015-2016 years in var-ious spheres of legal reality:– local self-government;– the formation of the foundationd capital repairs of condominium houses;– pensions provision of ex-militaries;– legislative regulation of property valuation activity;– problem of execution of court decisions.The Constitutional Court of the Russian Federation many times violated the Constitution of the Russian Federation. Since the Constitutional Court has recognized the legal abolition of elections of mayors in cities and towns. Constitutional Court recognized a legal collection taxes from citizens for capital repairs of condominium houses of others. Very often in the Russian law enforcement the Constitutional Court adopts a politically motivated decision, although such decisions are strictly prohibited by law. Unfortunately, the Constitutional Court of the Russian Federation not adequately protect the rights of Russian citizens and organizations.The author comes to the conclusion of a big crisis of law enforcement caused of legal nihilism, rooted among the enforcers, is made in the article. Analyzing the examples of judicial practice author propose any ways out of crisis law enforcement.